Bioaccessibility of Polycyclic Aromatic Hydrocarbons (PAHs) in grilled meat: the effects of meat doneness and fat content - Hamidi, Elliyana Nadia; Hajeb, Parvaneh; Selamat, Jinap; Lee, Soo Yee; Abdull Razis, Ahmad Faizal (Multidisciplinary Digital Publishing Institute, 2021)
Exposure to polycyclic aromatic hydrocarbons (PAHs) through diet is gaining concern due to the risk it poses to human health. This study evaluated the bioaccessibility of PAHs contained in charcoal-grilled beef and chicken in different segments of the gastrointestinal tract (GIT) with regard to the degree of doneness and fat content of the meats. The levels of 15 PAHs in the grilled meat samples and bioaccessible fractions were determined using high-performance liquid chromatography (HPLC) equipped with PAH column, and UV and fluorescence detectors. Total PAHs were found in beef (30.73 ng/g) and chicken (70.93 ng/g) before its digestion, and different PAHs’ bioaccessibility were observed in the different segments of GIT, with the highest in the stomach followed by the small intestine, despite the relatively higher bioaccessibility of individual PAHs in grilled beef as compared to those in grilled chicken. Additionally, the PAHs’ bioaccessibility increased with the increase in the degree of doneness. Positive linear correlation was observed for the PAHs’ bioaccessibility and the fat contents of grilled meat. Overall, this study highlights the influence of meat doneness (cooking time) and fat contents on the bioaccessibility and bioaccumulation of PAHs.